Analysing the conditions for establishing vicarious liability in Malaysia / Mohd Safri Mohammed Naaim … [et al.] - Mohammed Naaim, Mohd Safri; Abdul Jamal, Jusniza; Shaari@Mat Saman, Nurulhasni; Jaiman, Cartaz Ummu Syawaeda; Abdullah, Farhah (Universiti Teknologi MARA, Sabah, 2023)
Amidst the realm of employment scenarios, there are cases where an employee’s actions caused injury to their victims. Generally, an employer may be held vicariously liable for its employee’s actions, subject to several conditions. The research found that while the concept of vicarious liability has been long recognised in Malaysia, there is still a question over the test used by the court in determining “the course of employment.” The test to determine “the course of employment” has evolved over time, transitioning from “frolic of his own” to a “close connection test,” as affirmed in GMP Kaisar Security (M) Sdn Bhd v Mohamad Amirul Amin Bin Mohamed Amir [2022] 6 MLJ 369. In this case, the Federal Court held that the employee’s shooting was closely connected to his employment, and that it would be fair and just to hold the employer vicariously liable, despite the fact that his actions may have been unauthorised by the employer. However, this flexible approach may offer limited protection to the latter. This research therefore aims to analyse the conditions for establishing vicarious liability in Malaysia, particularly the test employed by the court, to determine whether the defendant’s actions fall within the course of employment. This research adopts a doctrinal approach involving a detailed analysis of the relevant case law and scholarly writing related to this area.